A multi‐country cross‐sectional study to assess predictors of daily versus on‐demand oral pre‐exposure prophylaxis in youth from South Africa, Uganda and Zimbabwe. Issue 8 (24th August 2022) - Dietrich, Janan Janine; Ahmed, Nadia; Webb, Emily L.; Tshabalala, Gugulethu; Hornschuh, Stefanie; Mulaudzi, Mamakiri; Atujuna, Millicent; Stranix‐Chibanda, Lynda; Nematadzira, Teacler; Ssemata, Andrew Sentoogo; Muhumuza, Richard; Seeley, Janet; et al.
Abstract: Introduction: Sub‐Saharan Africa (SSA) carries the burden of the HIV epidemic, especially among adolescents and young people (AYP). Little is known about pre‐exposure prophylaxis (PrEP) uptake and preferences among AYP in SSA. We describe preferences for daily and on‐demand PrEP among AYP in South Africa, Uganda and Zimbabwe. Methods: A cross‐sectional survey was conducted in 2019 among 13‐ to 24‐year olds, capturing socio‐demographics, HIV risk behaviours and preferences for daily or on‐demand PrEP. Logistic regression models were used to estimate odds ratios, adjusting for site, sex and age. Results and discussion: A total of 1330 participants from Cape Town ( n  = 239), Johannesburg ( n  = 200), Entebbe ( n  = 491) and Chitungwiza ( n  = 400) were enrolled; 673 (51%) were male, and the median age was 19 years (interquartile range 17–22 years). Of 1287 participants expressing a preference, 60% indicated a preference for on‐demand PrEP with differences by site ( p  < 0.001), sex ( p  < 0.001) and age group ( p  = 0.003). On‐demand PrEP was most preferred in Entebbe (75%), among males (65%) versus females (54%) and in older participants (62% in 18‐ to 24‐year‐olds vs. 47% in 13‐ to 15‐year‐olds). After adjusting for site, sex and age group, preference for on‐demand PrEP decreased as sex frequency over the past month increased ( p ‐trend = 0.004) and varied with the number of partners in the last 6 months, being least popular among those reporting four or more partners ( p  = 0.02). Participants knowing further in advance that they were likely to have sex were more likely to prefer on‐demand PrEP ( p ‐trend = 0.02). Participants having a larger age gap with their most recent partner and participants whose last partner was a transactional sex partner or client were both less likely to prefer on‐demand compared to daily PrEP ( p  = 0.05 and p  = 0.09, respectively). Participants who knew their most recent partner was living with HIV or who did not know the HIV status of their most recent partner were less likely to prefer on‐demand PrEP ( p  = 0.05). Conclusions: Our data show that AYP in four SSA communities prefer on‐demand over daily PrEP options, with differences seen by site, age and sex. PrEP demand creation needs to be reviewed, optimized and tailored to socio‐demographic differences and designed in conjunction with AYP.